The Effect of Recombinant Human Brain Natriuretic Peptide Combined with Xinmailong on Heart Failure and Its Impact on Cardiac Function and Inflammatory Response - Ge Z; Li C; Liu Y; Sun X (International Journal of General Medicine)
Zhaorui Ge,1,* Chunyan Li,2,* Yanling Liu,3 Xiujuan Sun4 1Department of Internal Medicine, Xianxian Hospital of Traditional Chinese Medicine, Xianxian, 062250, People’s Republic of China; 2Department of Cardiology, The Second Affiliated Hospital of Hebei North University, Baoding, People’s Republic of China; 3Wuqiao County Hospital of Traditional Chinese and Western Medicine Internal medicine, Wuqiao County, People’s Republic of China; 4Department of Cardiology, Wuqiao County Hospital of Integrated Chinese and Western Medicine, Wuqiao County, People’s Republic of China*These authors contributed equally to this workCorrespondence: Chunyan Li, Email yds734@126.comObjective: To analyze the effect of recombinant human brain natriuretic peptide (rhBNP) combined with Xinmailong on heart failure and its impact on cardiac function and inflammatory response.Methods: A retrospective analysis was conducted on the clinical data of 60 heart failure patients treated in our hospital from January 2023 to March 2024. The patients were included as research subjects to ensure the sample was representative. According to the different treatment methods, the patients were divided into two groups: the control group received only rhBNP treatment, and the experimental group received combined treatment with rhBNP and Xinmailong injection, with 30 patients in each group. The clinical effects, cardiac function, inflammatory response, and ventricular remodeling indicators of the two groups before and after treatment were observed and compared.Results: The total clinical effective rate of the experimental group was significantly higher than that of the control group (P< 0.05). After treatment, the NT-proBNP level in the experimental group was significantly lower than that in the control group (P< 0.05). After treatment, the levels of IL-6, TNF-α, and CRP in the experimental group were significantly lower than those in the control group (P< 0.05). After treatment, the LVESD and LVEDD levels in the experimental group were significantly lower than those in the control group, while the LVEF level was higher in the experimental group than in the control group (P< 0.05). There was no significant difference in the adverse event incidence between the two groups (P> 0.05). The 6-minute walk test (6 MWT) level in the experimental group was significantly higher than in the control group (P< 0.05).Conclusion: Recombinant human brain natriuretic peptide combined with Xinmailong is effective in treating heart failure, significantly improving cardiac function, reducing inflammatory responses, and reversing ventricular remodeling. It is also safe and beneficial for the patients’ prognosis.Keywords: heart failure, recombinant human brain natriuretic peptide, Xinmailong injection, inflammatory response, ventricular remodeling